A media surveillance analysis of COVID-19 workplace outbreaks in Canada and the United States - Shelby Fenton; Emma K Quinn; Ela Rydz; Emily Heer; Hugh W Davies; Robert A Macpherson; Christopher B McLeod; Mieke W Koehoorn; Cheryl E Peters (Canadian Science Publishing, 2022)
A media surveillance analysis was conducted to identify COVID-19 workplace outbreaks and associated transmission risk for new and emerging occupations. We identified 1,111 unique COVID-19 workplace outbreaks using the Factiva database. Occupations identified in the media articles were coded to the 2016 National Occupational Classification (V1.3) and were compared and contrasted with the same occupation in the Vancouver School of Economics (VSE) COVID Risk/Reward Assessment Tool by risk rating. After nurse aides, orderlies, and patient service associates (n = 109, very high risk), industrial butchers and meat cutters, and poultry preparers and related workers had the most workplace outbreaks reported in the media (n = 79) but were rated as medium risk for COVID-19 transmission in the VSE COVID Risk Tool. Outbreaks were also reported among material handlers (n = 61) and general farm workers (n = 28), but these occupations were rated medium-low risk and low risk, respectively. Food and beverage services (n = 72) and cashiers (n = 60) were identified as high-risk occupations in the VSE COVID Risk Tool. Differences between the media results and the risk tool point to key determinants of health that compound the risk of COVID-19 exposure in the workplace for some occupations and highlight the importance of collecting occupation data during a pandemic.